Lazy Wave Flexible Riser Dynamic Responses Analysis with Variation of SPM Offset from PLEM on Operation Condition - Muhammad Naufal Hawari; Wisnu Wardhana; Murdjito Murdjito (International Journal of Offshore and Coastal Engineering, 2025)
The increasing use of flexible risers in oil and gas exploration projects is a big challenge for engineers to design better riser systems to improve further the efficiency and safety of exploration and production activities in offshore oil and gas fields. SPM is often used as an offloading facility connecting FSO or FPSO as recipients of oil and gas products from subsea templates or wells. Under operating conditions, SPM can move freely following the movement of environmental loads. Drifting or changes in position due to the load on the SPM can threaten the riser response, whereas the riser response can be different whether the SPM is moving or drifting in its stress or bending response. The results in this study also contain the effect of this phenomenon on their fatigue life. As a result, the difference in riser response due to the distance from SPM to PLEM is that the farther the distance from SPM from PLEM, the greater the stress response and bending radius it has. Fatigue life also follows the same results, where the farthest distance from the SPM configuration to PLEM has the lowest fatigue life compared to the closest distance from the SPM to PLEM configuration, with the highest fatigue life at 128.31 years and the lowest at 124.78 years.